Assessing the Farmer’s Sustainable Livelihood Outcome of Rice Sectors Development in Sarawak - Sharon, Hou Wan; Rosita, Hamdan; Audrey, Liwan (Human Resource Management Academic Research Society (HRMARS), 2025)
This study aims to identify the relationship between the production, socioeconomic and environmental factors, and the sustainable livelihood outcomes of the farmers in Sarawak. The research was carried out in ten sites across the Miri and Kuching divisions. This research conducted a qualitative analysis that utilised an empirical approach. Interviews were conducted with thirty selected respondents to acquire information about rice production and livelihood strategies. The study indicated that land size, capital, subsidies, and incentives significantly influence rice output and farmers' livelihoods. Consequently, governmental action to standardise the Guaranteed Minimum Price rate between Sarawak and Peninsular Malaysia is vital for enhancing the farmers' income. Paddy cultivation land must be conserved and formally designated to avert its transformation into cash crop plantations and to ensure the viability of paddy agriculture in Sarawak. This study emphasises the significance of equitable rice pricing and land preservation for paddy farmers in Sarawak. It underscores the necessity of considering issues beyond output levels in the pursuit of sustainable living and the mitigation of climate change. Ultimately, governmental involvement and contemporary agricultural practices will be necessary to guarantee food security, enhance the quality of life for farmers, and assure the sustainable profitability of paddy cultivation in Sarawak.